Women’s Double Burden: Balancing Domestic and Professional Spheres - Radine Salsabila; Kholida Ulfi Mubaroka (Saree: Research in Gender Studies, 2026)
This study discusses the phenomenon of double burden experienced by women in Jelun Village, Banyuwangi, who must carry two main responsibilities: working in the public sphere and managing household duties. Although they actively contribute to the family economy through farming, trading, and other informal jobs, household tasks such as cooking, washing, and taking care of children remain their primary obligations. This condition displays that social and economic changes in rural areas have not fully altered traditional gender-based role divisions. The research uses a descriptive qualitative approach, with data collected through in-depth interviews with three informants and documentation. The findings reveal that women in Jelun Village demonstrate high resilience in balancing these multiple responsibilities, even when facing physical exhaustion and emotional stress. Values of hard work, patience, and responsibility play an important role in helping them endure daily challenges. However, behind this strength, the influence of patriarchy remains strong, positioning women as the main caretakers of domestic affairs. This situation indicates that gender equality in rural areas has not yet been fully achieved. Therefore, there is a need to increase social awareness and encourage a fairer division of household roles, so that women can participate more equally in both public and domestic spheres without being overburdened.   Abstrak Penelitian ini mengkaji fenomena peran ganda yang dialami oleh perempuan di Desa Jelun, Banyuwangi, yang harus menjalankan dua tanggung jawab utama, yaitu bekerja di ranah publik dan mengelola tugas domestik. Meskipun mereka berkontribusi aktif dalam perekonomian keluarga melalui kegiatan bertani, berdagang, dan pekerjaan informal lainnya, tugas rumah tangga seperti memasak, mencuci, dan merawat anak tetap menjadi kewajiban utama mereka. Kondisi ini menunjukkan bahwa perubahan sosial dan ekonomi di wilayah pedesaan belum sepenuhnya mengubah pembagian peran berbasis gender yang tradisional. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan teknik pengumpulan data berupa wawancara mendalam terhadap tiga informan serta dokumentasi. Hasil penelitian menunjukkan bahwa perempuan di Desa Jelun memiliki tingkat ketahanan yang tinggi dalam menjalankan berbagai tanggung jawab tersebut, meskipun menghadapi kelelahan fisik dan tekanan emosional. Nilai-nilai kerja keras, kesabaran, dan tanggung jawab memiliki peran yang signifikan dalam membantu mereka menghadapi tantangan sehari-hari. Namun, di balik ketangguhan tersebut, pengaruh patriarki masih kuat, karena terus menempatkan perempuan sebagai penanggung jawab utama urusan domestik. Kondisi ini mengindikasikan bahwa kesetaraan gender di wilayah pedesaan belum sepenuhnya tercapai. Oleh karena itu, diperlukan peningkatan kesadaran sosial serta pembagian peran yang lebih adil dalam rumah tangga agar perempuan dapat berpartisipasi secara lebih seimbang di ranah publik dan domestik tanpa mengalami beban yang berlebihan.